2022
DOI: 10.3168/jds.2021-20572
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces cerevisiae fermentation products reduce bacterial endotoxin concentrations and inflammation during grain-based subacute ruminal acidosis in lactating dairy cows

Abstract: Subacute ruminal acidosis (SARA) is a metabolic disorder in dairy cows that is associated with dysbiosis of rumen and hindgut microbiomes, translocation of immunogenic compounds from the gut lumen into blood circulation, and systemic inflammatory response. In this study we hypothesized that Saccharomyces cerevisiae fermentation products (SCFP) attenuate the increases in ruminal and peripheral bacterial endotoxin concentrations and the inflammation resulting from repeated induction of SARA. Lactating Holstein d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…The causes of this result are probably the decreased lipolysis and ruminal biohydrogenation of dietary fatty acids under the low ruminal pH [47] or the insu cient supply of endogenous fatty acids from liver and adipose tissue [48,49] . Previous studies have shown that grainbased SARA increases ruminal and peripheral bacterial endotoxin concentrations [50] . Zebeli Q et al [51] found that ruminal endotoxin concentration was negatively correlated with plasma TCHO concentration.…”
Section: Discussionmentioning
confidence: 99%
“…The causes of this result are probably the decreased lipolysis and ruminal biohydrogenation of dietary fatty acids under the low ruminal pH [47] or the insu cient supply of endogenous fatty acids from liver and adipose tissue [48,49] . Previous studies have shown that grainbased SARA increases ruminal and peripheral bacterial endotoxin concentrations [50] . Zebeli Q et al [51] found that ruminal endotoxin concentration was negatively correlated with plasma TCHO concentration.…”
Section: Discussionmentioning
confidence: 99%
“…These differences on CORT recorded levels could be related with the high variability of this parameter and low sampling frequency applied in this research. Moreover, it is proposed that the functional metabolites, organic acids, vitamins, and antioxidants present in the yeast cells’ wall, one of the active ingredients in OMNG, may either be used as nutrients by the rumen and gut microbiota or act as signaling molecules affecting interactions between microbes and the immunological response [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, Kent-Dennis et al ( 2020) observed that a short-term SARA challenge reduced the expression of several genes related to inflammatory responses, suggesting that SARA reduced this response. In addition, Guo et al (2022) observed that moderate grain-induced SARA did not increase the concentration of myeloperoxidase in rumen papillae, which suggests that these papillae were not inflamed. Hence, the acute phase response observed during SARA may be partially due to an inflammatory response in the reticulo-ruminal epithelium.…”
Section: Effects Of Sara On Epithelia Of the Gitmentioning
confidence: 88%
“…This translocation causes local inflammation and the passage of these toxins to the portal circulation and into the peripheral circulation, which can cause systemic inflammation. This inflammation is innate and consists of moderate changes in the concentrations of proinflammatory cytokines and moderate changes in the concentrations of acute phase proteins in blood, including increases in the concentrations of SAA, Hp, and LBP in peripheral blood (Zebeli and Metzler-Zebeli, 2012;Li et al, 2016;Guo et al, 2022). The moderate nature of this immune response may be due to the relatively low immunogenicity of ruminal LPS compared with LPS from pathogenic bacteria, such as E. coli (Plaizier et al, 2012(Plaizier et al, , 2018.…”
Section: Effects Of Sara On Epithelia Of the Gitmentioning
confidence: 99%